Women and crisis pregnancy : a report presented to the Department of Health and Children - MAHON, EVELYN (Stationery Office, 1998)
In June 1995, the Minister for Health, Michael Noonan, commissioned this study on women and crisis pregnancy in Ireland. The study was commissioned to identify the factors which contributed to the incidence of unwanted pregnancy and those which resulted in abortion. In this report, the decision making processes and the factors which women consider when making decisions arising from crisis pregnancies are analysed. The purpose of the research is to assist in the development and planning of future health policy with a view to reducing the incidence of abortion among Irish women. The format of the report is as follows. Chapter One sets the historical and social context in which crisis pregnancies are located. It reviews changes in birthrates, and the changing patterns of reproduction and marriage. It outlines the changes in women?s role in society over time and shows the manner in which motherhood has been modernised. The failure of state family policies to keep pace with these changes in gender roles is discussed. Chapter Two describes the methodology used in the study. The study initially had to find a sample of women who had crisis pregnancies. One group were immediately identifiable: those who were having abortions in England, and they formed one sample. Women who were planning on having their babies adopted formed a second sample and we located them in homes run by voluntary organisations. The final sample -- women with crisis pregnancies who planned to continue to become mothers -- had to be located from within the general population of pregnant women who were attending doctors, antenatal clinics and gynaecologists. This sample was generated using a short questionnaire which included a question on women?s initial response to their pregnancy and from this over three hundred in-depth interviews were conducted with women who had different responses to their pregnancies. This report on Women and Crisis Pregnancy is based on the analysis of qualitative interviews conducted with: eighty eight women who were having abortions, eleven women who were planning to have their babies adopted and, thirty four women with crisis pregnancies who were continuing the pregnancy to become mothers for the first time. Chapter Three analyses the data collected from 2,053 questionnaires completed by pregnant women who were attending for antenatal care. These were gathered as part of the process of generating a sample of pregnant women with crisis pregnancies. This data enabled us to generate some estimates on the extent of crisis pregnancies and to see the social parameters which help to construct a pregnancy as a crisis one. Chapter Four examines contraceptive behaviour and fertility control among all the sample of women with crisis pregnancies. It reviews changes in family planning practices, and access to contraception. It describes the factors which militated against their use of effective contraceptives and which resulted in their unplanned pregnancies. Chapter Five examines women?s access to, and use of crisis pregnancy counselling agencies prior to going to England. While twenty nine chose self-referral and did not consult anyone in Ireland, twenty one had contact with doctors in Ireland and thirty four had contact with an Irish based counselling agency. Women?s perceptions of counselling are also elaborated. Chapter Six examines the decision making processes of women who had abortions. It reviews the themes which framed their decision making: social stigma, the combination of work and family lives, the optimum conditions for childrearing and relationships with partners. It describes the coping strategies used in going through with an abortion. Chapter Seven describes the main influences on women?s decision to continue their pregnancies and become birth mothers, and then have their babies adopted. It examines the ways in which they rejected abortion while not being able to embrace lone motherhood.
PUBLISHED
Dublin
Keywords: crisis pregnancy